AIDA: Asteroid Impact and Deflection Assessment. (5th March 2015) - Michel, Patrick; Cheng, A.; Galvez, A.; Reed, C.; Carnelli, I.; Abell, P.; Ulamec, S.; Rivkin, A.; Biele, J.; Murdoch, N.
Abstract: AIDA (Asteroid Impact and Deflection Assessment) is a project of a joint mission demonstration of asteroid deflection and characterisation of the kinetic impact effects. It involves the Johns Hopkins Applied Physics Laboratory (with support from members of NASA centers including Goddard Space Flight Center, Johnson Space Center, and the Jet Propulsion Laboratory), and the European Space Agency (with support from members of the french CNRS/Cte dAzur Observatory and the german DLR). This assessment will be done using a binary asteroid target. AIDA consists of two independent but mutually supporting mission concepts, one of which is the asteroid kinetic impactor and the other is the characterisation spacecraft. The objective and status of the project will be presented.